SMART SAFETY JACKET FOR ARMY - Snehal Bhaskar Gaikwad; Pallavi Prakash Patil; Pradnya Chandrakant Sangar; Srushti Deepak Patil; Prof. Bongale Gaurav Ashok (International Journal of Innovations in Engineering Research and Technology, 2022)
As we all know that climate condition is changing continuously, the winter and summer season are getting much colder and warm, especially in northern region and western region of India. That’s why we develop a smart safety jacket for ARMY by using GPS, IOT, Different Sensors, control media device in the jacket. The smart safety Jacket aim for providing good health monitoring and track the position of sensor.